2007
DOI: 10.1088/0029-5515/47/11/007
|View full text |Cite
|
Sign up to set email alerts
|

Volume recombination of C4+in detached divertor plasmas of JT-60U

Abstract: Volume recombination of C4+ and e− into C3+ is observed for the first time in detached divertor plasmas with an X-point MARFE. The recombination zone is located around the X-point, and the electron temperature and density are evaluated to be 6.3 eV and 7.8 × 1020 m−3, respectively. In this zone, the volume recombination flux is larger by two orders of magnitude than the ionization flux of C3+. However, the radiation power due to the recombination process is only 2% of the total radiation power, measured by a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…If the C 3þ flux from the divertor region is higher than that from the main plasma, it is expected that auxiliary impurity seeded from the divertor, for instance, CD 4 , ionizes into C 3þ effectively and yields radiation efficiently, leading to high controllability of radiation loss. In contrast, if the C 3þ flux from the main plasma is higher than that from the divertor region, the controllability of the radiation loss by auxiliary impurity seeding may be low because of difficulties in controlling the transport via the main plasma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the C 3þ flux from the divertor region is higher than that from the main plasma, it is expected that auxiliary impurity seeded from the divertor, for instance, CD 4 , ionizes into C 3þ effectively and yields radiation efficiently, leading to high controllability of radiation loss. In contrast, if the C 3þ flux from the main plasma is higher than that from the divertor region, the controllability of the radiation loss by auxiliary impurity seeding may be low because of difficulties in controlling the transport via the main plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, if the C 3þ flux from the main plasma is higher than that from the divertor region, the controllability of the radiation loss by auxiliary impurity seeding may be low because of difficulties in controlling the transport via the main plasma. Recently, it is reported that at the X-point in the detached plasma with MARFE, the volume recombination of C 4þ is one of the processes to produce C 3þ and that the electron temperature is too low to ionize C 3þ to C 4þ [4]. Hence it is expected that C 4þ at the X-point is transported from the upstream via the main plasma, and is not originated from the lowly ionized carbon ions transported from the downstream of the divertor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For such a purpose, spectroscopy is often a method of choice and spectroscopic measurements of impurity line radiation are routinely used for plasma diagnostics. In tokamaks with carbon tiles, such as JT-60U, carbon line radiation is one of the dominant energy loss channels [1][2][3]. In this device, impurity radiation is dominated by C III and C IV line emission.…”
Section: Introductionmentioning
confidence: 99%
“…In this device, impurity radiation is dominated by C III and C IV line emission. Intensities of lines emitted by these two species are used for the electron temperature determination and its spatial distribution in the divertor [1][2][3]. Under detachment conditions of divertor plasmas, high-members of the Balmer series of hydrogen or its isotope deuterium are observed.…”
Section: Introductionmentioning
confidence: 99%